2017
DOI: 10.1080/09585176.2016.1240885
|View full text |Cite
|
Sign up to set email alerts
|

Fidelity to and satisfaction with prescribed curriculum in an Arab educational context: ESL teachers' perspective

Abstract: Educational institutions in the Arab Gulf are requiring rapid changes to enhance English language learning to keep up with globalization and economic growth. This urges the need for investigating policy changes such as effectiveness in curriculum orientations and their impact on the actual process of teaching in order to gauge how educational institutions are performing. This paper reports the findings of a survey study on curriculum enactment in the English Language Foundation Program of a higher education in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
7
0
2
Order By: Relevance
“…Furthermore, Gaytan [3]indicated that PLEs involve consuming externally hosted Web 2.0 facilities and tools intended to improve the sharing of learning resources and materials among learners. Moreover, Ellili-Cherif and Hadba [4] considered that these platforms help learners to managing their pedagogical practices and participating in the generation of cooperative knowledge. This is while, it should place the accountability for establishing learning on the learners, which makes it an integrally self-directed practice.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Gaytan [3]indicated that PLEs involve consuming externally hosted Web 2.0 facilities and tools intended to improve the sharing of learning resources and materials among learners. Moreover, Ellili-Cherif and Hadba [4] considered that these platforms help learners to managing their pedagogical practices and participating in the generation of cooperative knowledge. This is while, it should place the accountability for establishing learning on the learners, which makes it an integrally self-directed practice.…”
Section: Introductionmentioning
confidence: 99%
“…Semi‐structured interviews were conducted with teachers involved directly or indirectly in the reform process with a focus on their experience in schools at different stages of trialling new approaches. The constant factor for the Pioneer Lead teachers was their involvement in AoLE meetings; semi‐structured interviews allowed them to share their reflections on the experience (Ellili‐Cherif & Hadba, ; Peterson & Bentley, ).…”
Section: Methodsmentioning
confidence: 99%
“…Cynhaliwyd cyfweliadau lled‐strwythuredig ag athrawon a oedd yn ymwneud yn uniongyrchol neu’n anuniongyrchol â’r broses diwygio i drafod eu profiadau mewn ysgolion ar wahanol gamau wrth dreialu dulliau newydd. Un ffactor a oedd yn gyffredin i’r Athrawon Arloesi Arweiniol oedd eu bod yn cymryd rhan mewn cyfarfodydd ar Feysydd Dysgu a Phrofiad; roedd y cyfweliadau lled‐strwythuredig yn gyfle iddynt rannu eu meddyliau am y profiad (Ellili‐Cherif a Hadba, 2017; Peterson a Bentley, 2017).…”
Section: Dulliau Ymchwilunclassified